Ferroptosis, necroptosis and cuproptosis: Novel forms of regulated cell death in diabetic cardiomyopathy - Ke, Dan; Zhang, Zhen; Liu, Jieting; Chen, Peijian; Li, Jialing; Sun, Xinhai; Chu, Yanhui; Li, Luxin (Frontiers in Cardiovascular Medicine, 2023)
Diabetes is a common chronic metabolic disease, and incidence continues to increase year by year. Diabetic patients mainly die from various complications, with the most common being diabetic cardiomyopathy (DCM). However, the detection rate of diabetic cardiomyopathy is low in clinical practice, and a targeted treatment is lacking. In recent years, a large number of studies have confirmed that myocardial cell death in diabetic cardiomyopathy involves pyroptosis, apoptosis, necrosis, ferroptosis, necroptosis, cuproptosis, cellular burial and other processes. Most importantly, numerous animal studies have shown that the onset and progression of diabetic cardiomyopathy can be mitigated by inhibiting these regulatory cell death processes, such as by utilizing inhibitors, chelators, or genetic manipulation. Therefore, we review the role of ferroptosis, necroptosis and cuproptosis, three novel forms of cell death in diabetic cardiomyopathy, search for possible targets, and analyze the corresponding therapeutic approaches to these targets.